Brassinosteroids induced drought resistance of contrasting drought-responsive genotypes of maize at physiological and transcriptomic levels - Gillani, Syed Faheem Anjum; Zhuang, Zelong; Rasheed, Adnan; Haq, Inzamam Ul; Abbasi, Asim; Ahmed, Shakil; Wang, Yinxia; Khan, Muhammad Tajammal; Sardar, Rehana; Peng, Yunling (Frontiers in Plant Science, 2022)
The present study investigated the brassinosteroids-induced drought resistance of contrasting drought-responsive maize genotypes at physiological and transcriptomic levels. The brassinosteroids (BRs) contents along with different morphology characteristics viz, plant height (PH), shoot dry weight (SDW), root dry weight (RDW), number of leaves (NL), the specific mass of the fourth leaf, and antioxidant activities were investigated in two maize lines that differed in their degree of drought tolerance. The results relating to KEGG enrichment analysis showed that plant hormonal signal transduction, starch, and sucrose metabolism were augmented in both lines. In contrast, the phenylpropanoid biosynthesis was augmented in lines H21L0R1 and 478. Our results demonstrate drought-responsive molecular mechanisms and provided valuable information regarding candidate gene resources for drought improvement in maize crop. The differences observed for BRs content among the maize lines were correlated with their degree of drought tolerance, as the highly tolerant genotype showed higher BRs content under drought stress.